2020
DOI: 10.24083/apjhm.v15i3.433
|View full text |Cite
|
Sign up to set email alerts
|

Yogic Interventions for Psycho-Physical Well-Being Under Covid-19 Times & After

Abstract: Health indeed is Wealth. The Corona Virus Pandemic has impacted the best health-care systems world-wide; even as the world grapples with the massive loss of human life causing pain to millions. The Pandemic is no more just a medical health challenge; it has thrown up spiritual and emotional challenges as it is affecting our belief system.  Prevention is Better than Cure is the mantra. Since, there is no allopathic medicine solution available; people are adopting various measures like social distancing an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
(17 reference statements)
0
3
0
Order By: Relevance
“…Finally, there are some intervention studies that support the observational findings. A study investigated the impact of transcendent yoga practice in a group of 126 people in India, finding that after 30 days of practicing yoga exercises, most of the participants reported that their stress level decreased, they felt more energetic, their flexibility increased and they had better sleep habits (Malik & Sharma, 2020 ). In another study, conducted a randomized controlled trial with the aim of exploring the degree of intervention and the effect of group reminiscence therapy in combination with physical exercise on spiritual well-being of older adults after the outbreak of the COVID-19 epidemic.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, there are some intervention studies that support the observational findings. A study investigated the impact of transcendent yoga practice in a group of 126 people in India, finding that after 30 days of practicing yoga exercises, most of the participants reported that their stress level decreased, they felt more energetic, their flexibility increased and they had better sleep habits (Malik & Sharma, 2020 ). In another study, conducted a randomized controlled trial with the aim of exploring the degree of intervention and the effect of group reminiscence therapy in combination with physical exercise on spiritual well-being of older adults after the outbreak of the COVID-19 epidemic.…”
Section: Resultsmentioning
confidence: 99%
“…These results highlight the importance of public health measures that ensure the continuity of R/S activities during the pandemic and the training of healthcare professionals to address these issues 19.7/22 STROBE Mahamid et al ( 2021 ) To investigate the relationship between positive religious coping, perceived stress, and depressive symptoms in response to the emergence of coronavirus (COVID-19) Cross-sectional study ( n = 400 Palestinian adults) Scales: PSS, PMIR and CES-D-10 Positive religious coping is significantly related to a decrease in depressive symptoms among the sample of Palestinian adults, as well as a decrease in the perceived stress of the participants. Knowing that positive religious strategies can help improve the resilience and well-being of populations affected by the pandemic, it is necessary to carry out interventions that consider the religious and spiritual aspects of people 17.5/22 STROBE Mahmood et al ( 2021 ) To test the relationship between religious coping and health anxiety Cross-sectional study ( n = 408 Pakistani Muslims) SHAI Scale and Religiosity Scale Muslims in Pakistan who suffer from pandemic-induced anxiety use religiosity as a coping strategy to deal with life circumstances 19/22 STROBE Malik et al ( 2020 ) To evaluate the impact of the preventive measures undertaken through Yoga practice Cross-sectional study ( n = 126 people who perform yoga daily for 30 days) Telephonic interview with self-made questionnaires Performing Yoga regularly has improved control of the mind and body and enhances well-being. It also helped in boosting the immune system which can act as a preventive measure to COVID-19 14.5/22 STROBE Nodoushan et al ( 2020 ) To evaluate the physical health with the spiritual and mental health of pregnant women during the COVID-19 pandemic Cross-sectional study ( n = 560 pregnant women) Scales: DASS-21 and self-efficacy The spiritual health of pregnant women decreases when they have high stress levels.…”
Section: Methodsmentioning
confidence: 99%
“…Yoga and physical exercises have been found to prevent acute respiratory illness [12]. Breathing exercises have been reported in previous studies to enhance immunity, which helps combat viral infections subsequentially [13].…”
Section: Yoga and Physical Exercises Can Boost Immunity Against Coron...mentioning
confidence: 98%